Mr. Magoo (Buena Vista Pictures, Roadshow Distributors, 1997)
Myopic millionaire Mr. Quincy Magoo accidentlly takes possession of a cache of stolen gems and becomes the target of evil culprits. Despite their efforts, however, Magoo consistently escapes unharmed and remains oblivious to the dangers that surround him. Magoo ultimately nabs the villains with the help of his nephew Waldo and his trusting bulldog Angus.